A literature review of Bee Colony optimization algorithms - Gulati, Rishabh; Vats, Prashant (2014 Innovative Applications of Computational Intelligence on Power, Energy and Controls with their impact on Humanity (CIPECH), 2014)
Bee Colony optimization techniques are inspired by the high level of mutual intelligence shown by the natural bees in the food foraging process. It is a population based natural search algorithm which provides the base to solve metaheuristic computational optimization problems. In this paper we have carried out a literature review of the applications of BCO into various areas of computational problems where they prove their worth in providing optimized solutions. We have further carried out a tabular comparison of the work performed by the various researchers by applying the the BCO as optimization algorithms for solving the Optimization Problems.